Application of corticosteroids in dentistry - Jovanović Marija G.; Stojanović Simona M. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2018)
Corticosteroids (CS) are natural or synthetic hormones that affect nearly every aspect of human physiology. In the clinical sense, by reducing the symptoms of inflammation and immunosuppression, CS act symptomatically, decreasing problems of the underlying disease or the current state of the patient. According to application, corticosteroids are divided into topical, local and systemic way of use. Topical use of CS makes vasoconstriction, lowers mast cells degranulation, and reduces the permeability of capillaries reducing the amounts of released histamine from basophils and mast cells. The main goal of this therapy is to relieve or at least reduce pain in patients, which has an impact on overall health, nutrition, speech. Soft tissue inflammations that require the application of CS are: recurrent aphthous stomatitis, oral submucosal fibrosis, keloids and hypertrophic scars, mucocele; painful syndrome with manifestations in the head and neck: Bechet syndrome, pemfigoid syndrome, bullous pemfigoid,Oral Lichen planus, etc.; that reduces the need for taking analgetics .In oral surgery they are used for the treatment of the impacted wisdom teeth and other serious interventions which apart from analgesics (NSAIDS and narcotic analgesics) require CS in order to reduce trizmus, swelling and pain. There are numerous studies that suggest the time and route of the administration CS in lower impacted wisdom teeth surgery, as well as different combinations of CS with other medications in order to reduce morbidity this such an intervention. Local application of CS is indicated in this treatment of gigantocellular lesions and can replace the surgical procedures. Conclusion: Corticosteroids have wide application in dentistry in their indicational areas.